(untitled) (Journal of Universal Excellence, 2026)
Research Question (RV): How important is well-being of the employees in organization, what depends on it and what impact does the leadership of the organization have on it? Purpose: To explore the factors that affect the well-being on employees and find the ways to establish a good climate in the company. Method: With integrative literature review or researches that have been done on this area and with collecting data from USA, EU and Slovenia. Results: The results of all researches are not significantly different, because the well-being regardless of country and organization dependent on similar parameters. Good relationships with management, payment, edicational and personal growth opportunities, education, promotion and favorable working conditions. Organization: The impact on the organization is strong, because it enables the organization to achieve a better working climate, fewer abstences from work due to illness and result in lower costs and increased productivity of workers. Society: The well-being of people is influenced by a greater positive mindset and generally on less stressful life and a better health situation. Originality: We treat articles according to three different areas: Europe, the United States of America and Slovenia. The combined results are described using the Vennov diagram. Limitations/Future Research: Further research should explore measures and ways to help organizations in terms of innovation in workplaces for well-being and productivity of workers.